Factors associated with metachronous metastases and survival in locally advanced and recurrent rectal cancer. Issue 6 (28th August 2020) - Baird, D. L. H.; Kontovounisios, C.; Simillis, C.; Pellino, G.; Rasheed, S.; Tekkis, P. P.
Abstract : Background: Better understanding of the impact of metachronous metastases in locally advanced and recurrent rectal cancer may improve decision‐making. The aim of this study was to investigate factors influencing metachronous metastasis and its impact on survival in patients who have a beyond total mesorectal excision (bTME) operation. Methods: This was a retrospective study of consecutive patients who had bTME surgery for locally advanced and recurrent rectal cancer at a tertiary referral centre between January 2006 and December 2016. The primary outcome was overall survival. Cox proportional hazards regression analyses were performed. The influence of metachronous metastases on survival was investigated. Results: Of 220 included patients, 171 were treated for locally advanced primary tumours and 49 for recurrent rectal cancer. Some 90·0 per cent had a complete resection with negative margins. Median follow‐up was 26·0 (range 1·5–119·6) months. The 5‐year overall survival rate was 71·1 per cent. Local recurrence and metachronous metastasis rates were 11·8 and 22·2 per cent respectively. Patients with metachronous metastases had a worse overall survival than patients without metastases (median 52·9 months versus estimated mean 109·4 months respectively; hazard ratio (HR) 6·73, 95 per cent c.i. 3·23 to 14·00). Advancing pT category (HR 2·01, 1·35 to 2·98), pN category (HR 2·43, 1·65 to 3·59), vascular invasion (HR 2·20, 1·22 to 3·97) and increasing numbers of positive lymph nodes (HR 1·19, 1·07 to 1·16) increased the risk of metachronous metastasis. Nine of 17 patients (53 per cent) with curatively treated synchronous metastases at presentation developed metachronous metastases, compared with 40 of 203 (19·7 per cent) without synchronous metastases ( P  = 0·002). Corresponding median length of disease‐free survival was 17·5 versus 90·8 months ( P  < 0·001). Conclusion: As metachronous metastases impact negatively on survival after bTME surgery, factors associated with metachronous metastases may serve as selection tools when determining suitability for treatment with curative intent. Abstract : Surgery for locally advanced and recurrent rectal cancer can achieve good survival outcomes. Some histopathological features significantly increase the number of metachronous metastases and shorten survival. Presentation with a synchronous metastasis that is treated successfully significantly increases the number of metachronous metastases and shortens the time to subsequent metachronous metastasis. Patient selection is key for bTME Abstract : Antecedentes: Una mejor comprensión del impacto de las metástasis metacrónicas en el cáncer de recto localmente avanzado y recidivante puede mejorar la toma de decisiones. El objetivo de este estudio fue investigar los factores que influyen en las metástasis metacrónicas y su impacto en la supervivencia en pacientes sometidos a una operación más amplia que una escisión total del mesorrecto ( beyond total mesorectal excision, bTME). Métodos: Se trata de un estudio retrospectivo de pacientes consecutivos sometidos a operaciones bTME por cáncer de recto localmente avanzado y recidivante en un centro de referencia terciario entre enero 2006 y diciembre 2016. El resultado primario fue la supervivencia global. Se realizaron análisis de regresión de riesgos proporcionales de Cox. Se evaluó la influencia de las metástasis metacrónicas en la supervivencia. Resultados: De un total de 220 pacientes incluidos, 171 fueron tratados por tumores primarios localmente avanzados y 49 por una recidiva de cáncer de recto. Un 90% fue sometido a una resección completa con márgenes negativos. La mediana de seguimiento fue 260 meses (rango 1, 5 a 119, 6 meses). La supervivencia global a los 5 años fue del 71%. Las tasas de recidiva local y metástasis metacrónicas fueron del 11, 8% y del 22, 2%, respectivamente. Los pacientes con metástasis metacrónicas presentaron una supervivencia peor en comparación con los pacientes sin metástasis (mediana 46, 7 versus 109, 4 meses, cociente de riesgos instantáneos, hazard ratio, HR 6, 73, i.c. del 95% 3, 23–14, 00). Los factores que aumentaron el riesgo de metástasis metacrónicas fueron un estadio T patológico avanzado HR 2, 01 (i.c. del 95% 1, 35‐2, 98), estadio N HR 2, 43 (i.c. del 95% 1, 65‐3, 59), invasión vascular HR 2, 20 (i.c. del 95% 1, 22‐3, 97) y un número creciente de ganglios linfáticos positivos HR 1, 19 (i.c. del 95% 1, 07‐1, 16). En pacientes con metástasis sincrónicas tratadas con intención curativa de inicio, el 52, 9% desarrollaron metástasis metacrónicas versus el 19, 7% en pacientes sin metástasis sincrónicas ( P = 0, 002). La mediana de la supervivencia libre de enfermedad ( disease‐free survival, DFS) correspondiente fue de 17, 5 versus 90, 8 meses ( P < 0, 0001). Conclusión: Dado que las metástasis metacrónicas tienen un impacto negativo en la supervivencia tras cirugía bTME, los factores asociados con las metástasis metacrónicas pueden servir como variables de selección para decidir la idoneidad de un tratamiento con intención curativa.